Displacement damage stabilization by hydrogen presence under simultaneous W ion damage and D ion exposure. (5th July 2019) - Markelj, S.; Schwarz-Selinger, T.; Pečovnik, M.; Založnik, A.; Kelemen, M.; Čadež, I.; Bauer, J.; Pelicon, P.; Chromiński, W.; Ciupinski, L.
Abstract: Polycrystalline tungsten (W) samples were simultaneously irradiated by 10.8 MeV W ions and exposed to 300 eV deuterium (D) ions at different temperatures ranging from 450 K to 1000 K. After simultaneous W ion irradiation and D ion exposure the samples were additionally exposed to low-energy D ions at 450 K in order to populate all the defects created beforehand. The amount of damage created was evaluated by measuring D depth profiles and D thermal desorption spectra. Results were compared with data obtained in a sequential experiment where samples were first irradiated by 10.8 MeV W ions and only afterwards exposed to 300 eV D ions at 450 K to populate the created defects. At 450 K we observed a two times higher maximum D concentration for the simultaneous case as compared with the sequential case. At 600 K and 800 K the ratio between the simultaneous and sequential case decreases to about 1.6 and 1.2, respectively, and increases again to a factor of 2 at 1000 K. We attribute this dependence on temperature to the change in the concentration of mobile and trapped D during the simultaneous exposures, which is in line with theoretical calculations predicting that trapped D in a vacancy prevents vacancy annihilation with self-interstitials.